Parental Role Modeling in Shaping Children's Religious Character: A Qualitative Study on Religious Education Practices in the Family Environment - Susanti, Yulia Putri; Rambe, Khoirul Fadli; Rahmi, Elvi; Hilmi, Hilmi (Al-kayyis: Journal of Islamic Education, 2025)
This study aims to describe the role of parents as role models in children's religious learning. The background of this study is based on the phenomenon of the weakening of parental role models in everyday life, which has an impact on the low internalization of religious values in children. In fact, parents are the first and foremost educators who should be role models in religious behavior and practice. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation of several parents who work as fishermen. The results show that some parents are not yet able to set a good example in religious life, such as not performing religious duties consistently, using language that is not polite in front of children, and exhibiting behavior that does not reflect Islamic values. This weak role modeling has an impact on children's low enthusiasm and understanding of religious teachings. These findings emphasize the importance of strengthening the role of parents as role models in shaping children's religious character. The implications of this study encourage the need for parent training programs so that they can become consistent models of Islamic behavior, thereby creating a family environment that supports the optimal spiritual growth and development of children.